Elemen kunci pendorong partisipasi masyarakat sebagai fondasi kebijakan Smart City: Suatu kajian pustaka sistematis - Adriansyah Dhani Darmawan (Jurnal Kependudukan Indonesia, 2022)
This study aims to identify critical elements needed to enhance community participation in Smart City policies. Although several studies have discussed the role of citizens in smart cities, these studies focused only on one aspect, whether it was the societal aspect, government/municipality, or technology. In order to fill the gap in the literature, this study seeks to extract the important elements of citizen participation based on the three aspects as a whole by using the systematic literature review (SLR) method. The SLR method is useful for mapping comprehensively when information or knowledge about a particular topic is being developed with limited empirical evidence. A total of 103 articles published from 1999-2021 were analyzed as the unit of analysis for this study. There are 12 critical elements to encourage community participation, and all these elements should not be considered partially. This study argues that it is essential to synchronize each element to make substantive participation. By doing so, the community will have the opportunity to make a transformative impact on smart city development.